1966
DOI: 10.1111/j.1748-1716.1966.tb03415.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Types of Fat on the Cholesterol Distribution in the Rat

Abstract: Experiments were conducted with and without addition of 1 per cent cholesterol to diets containing 20 per cent of fats of the following types: 1. corn oil, 2. 19.5 per cent hydrogenated coconut oil and 0.5 per cent corn oil, and 3. 12 per cent hydrogenated coconut oil and 8 per cent olive oil. Following a 3 weeks' pre‐experimental period on a fat free diet adult female rats were given the experimental diets for 6 weeks. In rats given cholesterol corn oil caused the well known transfer of cholesterol from plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1966
1966
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The experiments presented here were done before the experiments in adult rats. (Gran and Nicolaysen 1966) were started. The erroneously high tissue cholesterol values obtained with the Tschugaeff method have been documented by us.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiments presented here were done before the experiments in adult rats. (Gran and Nicolaysen 1966) were started. The erroneously high tissue cholesterol values obtained with the Tschugaeff method have been documented by us.…”
Section: Resultsmentioning
confidence: 99%
“…The rats were killed at the conclusion of the experiments by a stunning blow over the neck and exsanguinated. The methods for tissue analyses have been described by Gran and Nicolaysen (1966).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results of the present study demonstrated that sugar cane rind has an effect on weight control of rats, showing a significant difference between groups II and IV. Kaunitz and Johnson (17), and Gran and Nicolaysen (18) reported that feeding vegetable oil, which contains a high percentage of polyunsaturated fatty acids decreases serum Chol in rats. In our present experiment, rats fed corn oil (containing over 50% linoleic acid) instead of lard (group III) resulted in showing a significantly lower serum Chol level.…”
Section: Discussionmentioning
confidence: 99%